Return Migrants and the Wage Premium : Does the Legal Status of Migrants Matter? - Elmallakh, Nelly; Wahba, Jackline (World Bank, Washington, DC, 2021)
This paper examines the impact of the legal status of overseas migrants on their wages upon return to the home country. Using unique data from the Arab Republic of Egypt, which allows distinguishing between return migrants according to whether their international migration was documented or undocumented, the paper examines the impact of illegal status on wages upon return. Relying on a conditional mixed process model, which takes into account the selection into emigration, return, and the legal status of temporary migration, the analysis finds that, upon return, undocumented migrants experience a wage penalty compared with documented migrants, as well as relative to non-migrants. The results are the first to show the impact of undocumented migration on the migrant upon return to the country of origin.